Human development and carbon dioxide emissions: Part II Alternative emission scenarios, policy and institutional issues. (4th August 2014) - Edmonds, J.; Darmstadter, J.
Greenhouse gases are products of human activity, and their production has increased as industrial development has increased. Increased production of these gases, of which carbon dioxide is the most significant, has affected global temperature and climate. The nature of future climatic change will depend upon the rate of emission of greenhouse gases, the capacity of mechanisms for their removal from the atmosphere, and the interaction between the composition of the atmosphere and the climate. This article deals with the first of these factors: the rate of emission. In Part I examination of this topic was split into consideration of the background to CO2 emissions and the long–term trends in emissions from fossil fuels. Here in Part II we examine alternative scenarios for future emissions, and discuss the feasibility of energy strategies designed to avert, mitigate or delay climatic changes.